Internalisasi Nilai Karakter melalui Kegiatan Ekstrakurikuler Pramuka di Madrasah - Rizal Abdul Aziz; Vita Fitriatul Ulya (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
Currently, as a medium for character education, scouts are a required extracurricular in elementary school. This research aims to determine the internalization of character values ​​through scout extracurricular activities. This research approach is a qualitative method that investigates character values established through scout extracurricular activities. Data collection techniques in this study used interviews, observation, and documentation. The subject of this study is scout coordinators, scout coaches, and students of classes 3, 4, 5 and 6 MI Istiqamah Singgahan Tuban. The study results show that scouting activities are done weekly or during school holidays. The current negative impact of developing science and technology affects the moral decadence of students, but scouting activities can establish good morals. The types of scout material taught and applied include PBB activities (Rules for the Rows), rigging, Morse code, semaphore, and exploration. Students' character values are cooperation, hard work, independence, discipline, and caring. Scout extracurriculars are carried out with fun learning methods so the students do not feel bored and have the spirit to participate in scouting activities.